Citizen, Territory and Technologies: Smart Learning Contexts and Practices Proceedings of the 2nd International Conference on Smart Learning Ecosystems and Regional Development - University of Aveiro, Portugal, 22-23, June 2017 - Mealha, Óscar; Divitini, Monica; Rehm, Matthias; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book gathers a selection of the articles accepted for presentation and discussion at the 2nd International Conference on Smart Learning Ecosystems and Regional Developments (SLERD 2017), held 22-23 June 2017 at the University of Aveiro, Portugal. What characterizes smart learning ecosystems? What is their role in city and regional development and innovation? How can we promote the engagement of citizens in smart learning ecosystems? These are some of the questions addressed at SLERD 2017 and documented here. The proceedings include scientific papers that endeavor to understand, devise and promote innovative human-centric design and development methods, education/training practices, informal social learning, and citizen-driven policies. The individual papers elaborate on the notion of smart learning ecosystems, study the relation of smart learning ecosystems with their territory, and identify vital resources for smart learning. As such, they help to foster the social innovation sectors, Information and Communication Technology (ICT) and economic development and deployment strategies, alongside new policies for smarter, proactive citizens - making them a valuable resource for researchers and policymakers alike.
Mobile Seamless Learning Tool for Cancer Education -- Reflecting on Co-Creating a Smart Learning Ecosystem for Adolescents with Congenital Brain Damage -- Creativity Enhanced by Technological Mediation in Exploratory Mathematical Contexts -- Meaningful Learning in U-Learning Environments: An Experience in Vocational Education -- The Classroom Physical Space as a Learning Ecosystem - Bridging Approaches: Results from a Web Survey -- A Review of Proxemics in 'Smart game-playing' -- The Diorama Project: Development of a Tangible Medium to Foster STEAM Education Using Storytelling and Electronics -- Automating Assessment of Exercises as Means to Decrease MOOC Teachers' Efforts -- DELTA: Promoting Young People Participation in Urban Planning -- Becoming a Mobile Internet User in a South African Rural Area: The Case of Women in Dwesa. .
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence